The Problems of Appointment Acting Officer of Regional Head in the Transition Period Before the Election of 2024: Problematika Pengisian Jabatan Penjabat Kepala Daerah di Masa Transisi Pra Pilkada 2024 - Rahmazani Rahmazani (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
The appointment of officials during the 2024 pre-election transition period was carried out by central government to fill the transitional period for regional heads due to the postponement of the regional elections. This research is intended to know the mechanism for filling the acting officer and concluding that the results of filling the positions referred to the optimal implementation of regional government. This research is an empirical legal research. The appointment of positions has been carried out by central government, but there is no measurable mechanism in the process because there are no specific rules governing this matter. The Constitutional Court has mandated to issue implementing regulations for Article 201 Law Number 10 Year 2016 so that placement of officer is within the corridors of a rule of law and democracy. Unfortunately the government did not heed the mandate, resulting in various problems in the process of appointing positions.